Pancer: A Music Interpretation of the Chronicle of Panjer | Pancer: Sebuah Musik Interpretasi Babad Panjer - I Gusti Agung Kresna Bayu Kepakisan; I Ketut Sudhana (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
This article discusses the percussion of the